Pengaruh kepemimpinan dan lingkungan kerja sosial terhadap kinerja pegawai PT Telekomunikasi Indonesia (Telkom) wilayah kota Tasikmalaya - Eded Tarmedi; Syamsul Hadi Senen; Desty Putri Djayanti (Business Education Program of Universitas Pendidikan Indonesia, 2020)
This research aims to find out the effectiveness of leadership, social work environment, and performance. The design of this study is cross sectional using an explanatory approach to surveys. The analysis unit used is a saturated sample of 100 employees. This research uses quantitative methods. With the data analysis technique used is a double linear regression with SPSS computer software version 26.0. The results of the study can be known that 1) the level of leadership is in a very high category, 2) the level of social work environment is in a very high category, 3) the performance level is in the high category, 4) leadership has an influence of 58.3% on performance, 5) the social work environment has an influence of 56.8% on performance, and 6) the influence of leadership and social work environment on performance is 70.7%. From the results of hypothetical testing research, it can be known that leadership and social work environment have a significant effect on performance.